Performance of sugarcane genotypes with early maturation in the ‘Zona da Mata’ region of Pernambuco State, Brazil - Albuquerque, Aurélia Pietrina Costa; Bastos, Gerson Quirino; Dutra Filho, João Andrade; Simões Neto, Djalma Euzébio; Silva, Leonam José; Souto, Lauter Silva (Comunicata Scientiae, 2016)
In sugarcane commercial cultivation the knowledge related to genotypes performance in different harvest seasons are essential for the identification of early genotypes which, when selected, will contribute to a significant increase in agroindustrial productivity. This study aimed to evaluate the agroindustrial performance of 26 sugarcane genotypes and to select genotypes that stood out for early maturation and a consequently early harvest. The experiments were conducted at ‘Olho D’gua’farm in the ‘Zona da Mata’ region, north of Pernambuco state. A randomized block design with four replications was used and the evaluated variables were: tons of pol per hectare (TPH), tons of sugarcane per hectare (TCH), fiber (FIB), adjusted pol% (PCC), soluble solids content (BRIX) and total recoverable sugar (ATR). The variance analysis and estimationof the genetic parameters were carried out, grouping the genotypes according to Scott-Knott´s test and a total economic analysis was realized. The average heritability for TPH and TCH indicates high possibility of success in the selection of early and highly productive genotypes. It was observed that the genotypes RB92579, RB867515, RB75126, RB942991, SP81-3250, RB93509, RB72454 and RB863129 presented better performance for an early harvest.